Cogeneration fuel cell-sorption air conditioning systems - Pilatowsky Figueroa, Isaac; SpringerLink (Online service). (London New York Springer-Verlag, 2011)
Although conventional cogeneration systems have been used successfully in the last two decades, most of them have been large units using mainly hydrocarbon fuels that are becoming increasingly expensive. New cogeneration systems based on fuel cells and sorption air conditioning systems promise to be an energy-saving alternative for situations when cooling, heating and power are needed at low and medium capacities. Cogeneration Fuel Cell-Sorption Air Conditioning Systems examines the thermodynamic principles of fuel cell performance and sorption air conditioning systems, and gives relevant information about the state of the art of these technologies. It also provides the reader with the theoretical bases and knowledge needed to understand the operation of these new cogeneration systems, as well as discussing the design basis and economical evaluation. Topics covered include: selected fuel cells for cogeneration CHP processes; state-of-the-art sorption refrigeration systems; potential applications in demonstration projects; and profitability assessment of the cogeneration system. Air conditioning and fuel cell engineers; postgraduates and researchers in energy fields; and designers of cooling, heating and power cogeneration systems will find Cogeneration Fuel Cell-Sorption Air Conditioning Systems a useful and informative reference.
1. Energy and Cogeneration -- 2. Thermodynamics of Fuel Cells -- 3. Selected Fuel Cells for Cogeneration CHP Processes -- 4. State-of-the-art Sorption Refrigeration Systems -- 5. Sorption Refrigeration Systems -- 6. Cogeneration Fuel Cells-Air Conditioning Systems -- 7. Potential Applications in Demonstration Projects -- 8. Profitability Assessment of the Cogeneration System.
Electronic reproduction.
Keywords: Cogeneration of electric power and heat; Electric power production; Fuel cells; Engineering; Electronic books